Transformation of 17α-Estradiol, 17β-Estradiol, and Estrone in Sediments Under Nitrate- and Sulfate-Reducing Conditions - Mashtare, Michael L; Lee, Linda S; Nies, Loring F; Turco, Ronald F (Environmental science & technology, 2013)
The natural manure-borne hormones, 17α-estradiol (17α-E2), 17β-estradiol (17β-E2), and estrone (E1), are routinely detected in surface water near agricultural land and wastewater treatment facilities. Once in the stream network, hormones may enter the sediment bed where they are subject to anaerobic conditions. This study focuses on the difference in anaerobic transformation rates and formation of metabolites from 17α-E2, 17β-E2, and E1 (applied at ∼3.66 μmol kg–1 of sediment on a dry weight basis) under nitrate- and sulfate-reducing conditions. Sediment extracts were analyzed using negative electrospray ionization tandem mass spectrometry. Under both redox conditions, degradation was stereospecific and followed similar trends in half-lives, 17β-E2 < 17α-E2 < E1, with degradation considerably slower under sulfate-reducing conditions. Both E2 isomers were predominantly converted to E1; however, isomeric conversion also occurred with peak concentrations of ∼1.7 mol % of 17β-E2 formed in 17α-E2 amended sediments and peak concentrations of ∼2.4 mol % of 17α-E2 formed from 17β-E2. In E1-amended systems, E1 transformed to E2 with preferential formation of the more potent 17β isomer up to ∼30 mol % suggesting that isomer interconversion is through E1. Sediments, therefore, may serve as both a sink and a source of the more estrogenic compound E2. Transformation of amended hormones in autoclaved sediments was markedly slower than in nonautoclaved sediments. Results support the inclusion of isomer-specific behavior and the potential for reversible transformation and interconversion in anaerobic sediments in modeling fate in stream networks and developing risk management strategies.